Metode Simple Additive Weigthing Pemberian Reward Karyawan Dalam Strategi Pemasaran Produk Kepada Konsumen - Rio Rahmat Yusran (JURIKOM (Jurnal Riset Komputer), 2022)
Marketing strategy is an effective way to increase competition whether it is engaged in goods or services. The marketing strategy is the most suitable way to arrange plans to obtain maximum results. The problem that occurs is the company's difficulty in providing Rewards to employees in carrying out strategies to increase company turnover. The main objective of this research is to make it easier for companies to give Rewards to employees who sell a lot of products to consumers as well as unique employee strategies that are suitable for increasing sales obsets to consumers. To improve marketing strategies to consumers, there are 5 criteria that must be implemented by employees including Planned market targets, Conventional Marketing, digital marketing, Updating the latest trends, and establishing good relations with customers. To complete this research, researchers used the Simple Additive Weight method. (SAW), in which this method performs the calculation process for each criterion weight by selecting the highest weight with each criterion so that each total value of the weights of the results obtained will be the final decision. The criterion Bpbot value used is W=[ 0.35; 0.25; 0.10; 0.10; 0.20] With the results of the selected Criteria Results, the highest score is obtained, namely, 1 obtained on behalf of Fadli, and the lowest score is 0.417 on behalf of Susi.